HYPERTENSION AS DETERMINANT OF COGNITIVE DYSFUNCTION AMONG ELDERLY SUB-POPULATION - Darmaningrat, Cokorda Istri Agung Asvini; Harahap, Herpan Syafii; Anggoro, Joko; Rianawati, Sri Budhi (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: Cognitive dysfunction is one of the main impacts of hypertension in the elderly population. Early detection and adequate management of early-stage cognitive dysfunction in hypertensive elderly is expected to improve their cognitive status and quality of life. Objective: This study aimed to determine the association between hypertension and cognitive dysfunction in a sub-population of the elderly in Mataram, Indonesia. Methods: This cross-sectional study involved elderly sub-population recruited consecutively in three public health centers in Mataram, Indonesia. Data included in this study were age, gender, occupation, educational level, hypertension, diabetes mellitus, and cognitive status. Cognitive status was assessed using the Indonesia version of Montreal Cognitive Assessment instrument. Multiple logistic regression analysis was performed to test whether hypertension was a determinant of cognitive dysfunction in participants taking into account the presence of socio-demographic status and diabetes mellitus as another vascular risk factor. Results: This study included 88 elderly as eligible participants. The frequency of cognitive dysfunction among participants was 61.4%. Multiple logistic regression analysis revealed that hypertension was the single variable significantly associated with a high frequency of cognitive dysfunction in elderly sub-population (odds ratio = 3.7; 95% confidence intervals = 1.3 – 10.4; p = 0.014). Conclusion: The frequency of cognitive dysfunction in the elderly sub-population in Mataram was high, amounting to 61.4%. Hypertension was the determinant of this high frequency of cognitive dysfunction in the sub-population studied.